2019
DOI: 10.3390/su11184860
|View full text |Cite
|
Sign up to set email alerts
|

Linking Land Use Metrics Measured in Aquatic–Terrestrial Interfaces to Water Quality of Reservoir-Based Water Sources in Eastern China

Abstract: The effects of anthropogenic land use on the water quality of reservoir-based water sources are understudied. We trained a self-organizing map (SOM) to measure the spatial pattern of nutrients over the course of a year in 61 reservoirs located in eastern China. In the linear regression model and one-way analyses of variance, we found that water quality was influenced by period of the year (flood, low, and normal periods based on rainfall conditions) and reservoir altitude (plains vs. mountains). Our results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…As areas with weak synergies were mostly located in a region with a relatively developed economy and intensive human activities, food production and regulating services were both at a relatively low level (Figures 2 and 4). Therefore, for these areas, on the one hand, it is necessary to strengthen the management of land-use types, especially at the county scale, set up ecological red lines [76], implement the Grain for Green Project (GFGP) [77], improve the supply capacity of stock, carbon sequestration, water conservation, and flood mitigation services, and alleviate the strong trade-off between services. On the other hand, the government could improve the utilization rate of water and soil resources through scientific irrigation and farming methods, aiming to achieve the high yield, high quality, and high efficiency of crops.…”
Section: Multiscale Characteristics Of Ess Trade-offs and Synergiesmentioning
confidence: 99%
“…As areas with weak synergies were mostly located in a region with a relatively developed economy and intensive human activities, food production and regulating services were both at a relatively low level (Figures 2 and 4). Therefore, for these areas, on the one hand, it is necessary to strengthen the management of land-use types, especially at the county scale, set up ecological red lines [76], implement the Grain for Green Project (GFGP) [77], improve the supply capacity of stock, carbon sequestration, water conservation, and flood mitigation services, and alleviate the strong trade-off between services. On the other hand, the government could improve the utilization rate of water and soil resources through scientific irrigation and farming methods, aiming to achieve the high yield, high quality, and high efficiency of crops.…”
Section: Multiscale Characteristics Of Ess Trade-offs and Synergiesmentioning
confidence: 99%
“…The regional and global impacts of climate change on reservoirs have become highly important. Reservoirs are critical resources in freshwater ecosystems that perform various functions, such as providing drinking water, regulating climate, maintaining biodiversity, and nitrate cycling [2]. However, pressure and competition for sustainable water management in reservoirs are increasingly exacerbated by human-induced factors, such as agricultural practices, urbanization, and industrialization [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is generated from surface water bodies, which provide drinking water, preserve biodiversity, control climate, and maintain phosphorus and nitrate cycling [1]. However, in recent decades, the quality of these water bodies has been threatened by anthropogenic activities (e.g., urbanization, agriculture, water extraction, sewage discharge) [2][3][4][5]. Therefore, in the management plan of pollution control at a watershed scale, a worthwhile initial step is the identification of the pollution sources.…”
Section: Introductionmentioning
confidence: 99%
“…On its side, the SOM has the advantages of providing a suitable representation of non-linear processes, as well as a large number of parallel distributed structures, and is capable of learning and induction. Ding et al [4] used the SOM training to improve linear techniques to identify the temporal and spatial patterns of several water quality variables. The authors found that the sampling-site elevation affected the water quality throughout different seasons.…”
Section: Introductionmentioning
confidence: 99%